Analysis Of Drinking Water Treatment At Regional Public Drinking Water Company or Perumda Drinkinng Water Tirta Mayang Jambi City - Farah Luthfiyah Putri Susanto; Dwi Noerjoedianto; Oka Lesmana S; Fajrina Hidayati; Ashar Nuzulul Putra (CV. AFDIFAL MAJU BERKAH, 2025)
The Batanghari River serves as the primary source of raw water for the Regional Drinking Water Company (Perusahaan Umum Daerah Air Minum/Perumda) Tirta Mayang in Jambi City. Over the past five years, the declining quality of river water has required more complex treatment processes to meet drinking water standards. The main reference for water quality parameters in the water treatment system at Perumda Tirta Mayang is the Indonesian Ministry of Health Regulation No. 492 of 2010. In addition to the deteriorating water quality of the Batanghari River, one of the major challenges faced by Perumda Tirta Mayang is frequent pipe leakage and recurring water supply interruptions, which often cause inconvenience for the community. This study employed a qualitative descriptive approach. The descriptive method was used to portray the current condition of the research subject based on observable facts, employing techniques such as in-depth interviews, field observations, and document analysis. The results of this study show that although the raw water quality requires extensive treatment, the final processed water meets the required standards. Moreover, the challenges encountered in the water treatment process can be effectively addressed through strong coordination and collaboration within the company